The gap between entitlement and access to healthcare: An analysis of "candidacy" in the help-seeking trajectories of asylum seekers in Montreal. (June 2017) - Chase, Liana E.; Cleveland, Janet; Beatson, Jesse; Rousseau, Cécile
Abstract: In 2012 the Canadian government made significant cuts to its historically strong federal refugee health coverage plan. While this policy had negligible effects on the level of coverage provided to asylum seekers in Quebec, there is evidence that this group nonetheless experienced reduced healthcare access during the period of polarized national debate that ensued. This study engaged the "candidacy" model of healthcare access to illuminate factors contributing to the observed gap between entitlement and access. Twenty-five semi-structured interviews were conducted with asylum seekers in Montreal to elicit narrative accounts of difficulties encountered in the pursuit of healthcare. Thematic content analysis in conjunction with a holistic examination of help-seeking trajectories revealed several important barriers to obtaining care, including widespread confusion and misinformation about refugee health coverage, cumbersome administrative procedures specific to asylum seekers, and long wait times. Feelings of marginalization and insecurity associated with precarious migratory status appeared to amplify the effects of these barriers to care such that even a minor access difficulty could have dramatic effects on future help-seeking and access outcomes. Demonstrating awareness of public discourses interrogating their deservingness of health coverage, participants often interpreted access difficulties as evidence of health professionals' unwillingness to serve them. Such interpretations conspired with fears associated with the asylum claim process to suppress self-advocacy, further help-seeking, and at times even information-seeking. This finding is particularly significant in that it suggests a mechanism through which hostile public representations of forced migrants–increasingly prevalent in Western host countries–can themselves endanger the physical, psychological, and social health of highly disadvantaged populations, even in the presence of strong entitlement policies. We close with reflections on how theoretical models of healthcare access might be adjusted to better accommodate the unique experiences of precarious status migrants. Highlights: Asylum seekers in Quebec faced difficulty accessing healthcare after 2012 reforms. Despite strong provincial coverage, they were often charged for or denied services. Negative public representations of asylum seekers shaped their access experiences. After initial access difficulties, many were afraid to seek information or recourse. Findings show how hostile public discourse can lead to adverse health outcomes.